Advanced gastric cancer: the value of surgery - Fugazzola, Paola; Ansaloni, Luca; Sartelli, Massimo; Catena, Fausto; Cicuttin, Enrico; Leandro, Gioacchino; de' Angelis, Gian Luigi; Gaiani, Federica; Di Mario, Francesco; Tomasoni, Matteo; Coccolini, Federico (Acta Biomedica Atenei Parmensis, 2018)
Gastric cancer is a common disease with high mortality. The definition of advanced gastric cancer is still debated. Radical surgery associated to appropriate systemic and intra-abdominal chemotherapy is the gold standard treatment. In presence of peritoneal carcinosis, reaching a complete cytoreduction is the key to achieve long-term survival. Adequate lymphadenectomy is also fundamental. Conversion therapy could be applied to selected IV stage patients. No definitive evidences exist regarding the oncological and surgical superiority of mini-invasive approaches over the classical open techniques.